Partisipasi Perempuan Dalam Pembangunan Manusia Berbasis Gender di Daerah Istimewa Yogyakarta - Tri Hesti Utami; Muhammad Arif (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
One of the main issues in human development is the issue of gender, where gender equality is a strategy that can be used to encourage the development of a region. Various government efforts have been made to achieve gender equality even though there are still disparities that exist between women and men in various fields. This study aims to determine the factors that influence the Gender Development Index in the Special Region of Yogyakarta in 2017-2021 by using the variables Gender Ratio, Women's Involvement in Parliament, Female Labor Force Participation Rate, and Women's Per Capita Expenditures. The data used in this study is secondary data and the method used is panel data regression through the Fixed Effect Model (FEM) approach. The results of this study indicate that the ratio of sex and expenditure per capita of women has no effect on the Gender Development Index (GDI). Meanwhile, the variables that have a positive effect on GDI in the Regency/City of the Special Region of Yogyakarta in 2017-2021 are Women's Involvement in Parliament and the Level of Participation in the Women's Labor Force. From this research it is hoped that it can help the government in its efforts to achieve gender equality and the government needs to pay attention again to issues of gender equality in the Special Region of Yogyakarta both in terms of labor, education, and in other fields so that there are no development gaps that occur between women and men.